Investigation of degradation mechanism of phosphorescent and thermally activated delayed fluorescent organic light-emitting diodes through doping concentration dependence of lifetime - Song, Wook; Kim, Taekyung; Lee, Jun Yeob; Lee, Yoonkyoo; Jeong, Hyein (Journal of industrial and engineering chemistry (Seoul, Korea), 2018)
[Display omitted] •Lifetime dependence on doping concentration in the phosphorescent and TADF organic light-emitting diodes.•Triplet–triplet annihilation as dominant degradation mechanism of phosphorescent devices.•Triplet–polaron annihilation as dominant degradation mechanism of TADF devices Lifetime study of blue phosphorescent and thermally activated delayed fluorescent organic light-emitting diodes was carried out to understand the dominant degradation process during electrical operation of the devices. Doping concentration dependence of the phosphorescent and thermally activated delayed fluorescent organic light-emitting diodes was studied, which demonstrated long lifetime at low doping concentration in the phosphorescent devices and at high doping concentration in the thermally activated delayed fluorescent devices. Detailed mechanism study of the two devices described that triplet–triplet annihilation is the main degradation process of phosphorescent organic light-emitting diodes, whereas triplet–polaron annihilation is the key degradation factor of the thermally activated delayed fluorescent devices.